Older Age Relates to Worsening of Fine Motor Skills: A Population-Based Study of Middle-Aged and Elderly Persons - Hoogendam, Yoo Young; van der Lijn, Fedde; Vernooij, Meike W.; Hofman, Albert; Niessen, Wiro J.; van der Lugt, Aad; Ikram, M. Arfan; van der Geest, Jos N. (Frontiers in Aging Neuroscience, 2014)
Introduction: In a population-based study of 1,912 community-dwelling persons of 45 years and older we investigated the relation between age and fine motor skills using the Archimedes spiral-drawing test. Also, we studied the effect of brain volume on fine motor skills. Methods: Participants were required to trace a template of a spiral on an electronic drawing board. Clinical scores from this test were obtained by visual assessment of the drawings. Quantitative measures were objectively determined from the recorded data of the drawings. As tremor is known to occur increasingly with advancing age, we also rated drawings to assess presence of tremor. Results: We found presence of a tremor in 1.3% of the drawings. In the group without tremor we found that older age was related to worse fine motor skills. Additionally, participants over the age of 75 showed increasing deviations from the template when drawing the spiral. Larger cerebral volume and smaller white matter lesion volume were related to better spiral drawing performance, whereas cerebellar volume was not related to spiral drawing performance. Conclusions: Older age is related to worse fine motor skills, which can be captured by clinical scoring or quantitative measures of the Archimedes spiral-drawing test. Persons with a tremor performed worse on almost all measures of the spiral-drawing test. Furthermore, larger cerebral volume is related to better fine motor skills.